La botanique (adaptée) pour les femmes dans la Bibliothèque universelle des dames - Łuczak, Barbara (Studia Romanica Posnaniensia, 2018)
In 1786 there appeared two volumes in the collection Bibliothèque universelle des dames which formed an elementary course of botany addressed to women. The course was based on Démonstrations élémentaires de botanique (Lyon, 1766), written by Marc-Antoine-Louis Claret of Flerieu de La Tourrette (in collaboration with François Rozier) for the use of students of the Royal Veterinary School. The purpose of this paper is to describe the way in which the authors adapted the botanical content for female readers.